Inference to the best explanation : the case of potential energy - Riggs, Peter J. (Array, 2020)
It has been claimed that kinetic energy is an objective physical quantity whilst at the same time maintaining that potential energy is not. However, by making use of the method of ‘inference to the best explanation’, it may be readily concluded that potential energy is indeed an objective physical quantity. This is done for an example drawn from the foundations of modern chemistry. In order to do so, the criteria of what counts as ‘most probable’ and ‘most reasonable’ are defined and then employed for choosing the best explanation.